Dynamics of pathogens and fecal indicators during riverbank filtration in times of high and low river levels. (1st February 2022) - Wang, He; Knabe, Dustin; Engelhardt, Irina; Droste, Björn; Rohns, Hans-Peter; Stumpp, Christine; Ho, Johannes; Griebler, Christian
Highlights: Relative removal of adenoviruses and fecal indicators during riverbank filtration was highest during flood events. Most efficient removal of pathogens takes place in the early sediment passage. Only a combination of bacterial and viral indicators is suitable for risk assessment at different hydrological situations. Floods and droughts pose a risk to water quality. Abstract: Riverbank filtration is an established and quantitatively important approach to mine high-quality raw water for drinking water production. Bacterial fecal indicators are routinely used to monitor hygienic raw water quality, however, their applicability in viral contamination has been questioned repeatedly. Additionally, there are concerns that the increasing frequency and intensity of meteorological and hydrological events, i.e., heavy precipitation and droughts leading to high and low river levels, may impair riverbank filtration performance. In this study, we explored the removal of adenovirus compared with several commonly used bacterial and viral water quality indicators during different river levels. In a seasonal study, water from the Rhine River, a series of groundwater monitoring wells, and a production well were regularly collected and analyzed for adenovirus, coliphages, E. coli, C. perfringens, coliform bacteria, the total number of prokaryotic cells (TCC), and the number of virus-like particles (TVPC) using molecular and cultivation-based assays. Additionally, basic physico-chemical parameters, including temperature, pH, dissolved organic carbon, and nutrients, were measured. The highest log10 reduction during the >72 m of riverbank filtration from the river channel to the production well was observed for coliforms (>3.7 log10 ), followed by E. coli (>3.4 log10 ), somatic coliphages (>3.1 log10 ), C. perfringens (>2.5 log10 ), and F + coliphages (>2.1 log10 ) at high river levels. Adenovirus decreased by 1.6–3.1 log units in the first monitoring well (>32 m) and was not detected in further distant wells. The highest removal efficiency of adenovirus and most other viral and bacterial fecal indicators was achieved during high river levels, which were characterized by increased numbers of pathogens and indicators. During low river levels, coliforms and C. perfringens were occasionally present in raw water at the production well. Adenovirus, quantified via droplet digital PCR, correlated with E. coli, somatic coliphages, TCC, TVPC, pH, and DOC at high river levels. At low river levels, adenoviruses correlated with coliforms, TVPC, pH, and water travel time. We conclude that although standard fecal indicators are insufficient for assessing hygienic raw water quality, a combination of E. coli, coliforms and somatic coliphages can assess riverbank filtration performance in adenovirus removal. Furthermore, effects of extreme hydrological events should be studied on an event-to-event basis at high spatial and temporal resolutions. Finally, there is an urgent need for a lower limit of detection for pathogenic viruses in natural waters. Preconcentration of viral particles from larger water volumes (>100 L) constitutes a promising strategy. Graphical abstract: Image, graphical abstract